TANGGAPAN ANATOMIS DARI BEBERAPA SUMBER BENIH Acacia manigum Willd. TERHADAP KONDISI CEKAMAN GARAM - Dwi Kartikaningtyas; Oktiva Quirena; nfn Suharyanto; Sri Sunarti (Jurnal Pemuliaan Tanaman Hutan, 2014)
Along with the increase of forest plantation development to supply raw material for industry, the utilization of marginal land with high salinity is likely to be an alternative for the plantation of A. mangium. In an effort to increase the improvement of A. mangium to be extensively planted on the widely alternative land, breeding programs were conducted to get trees of A. mangium which are tolerant to environmental stress, such as salt stress. The purpose of this study was to observe the anatomical response of A. mangium collected from several seed sources to salinity stress as a basis for salt tolerance breeding program. The trial consisted of four seed sources arranged in Completely Randomized Design with four level salt stresses(0; 22; 26 and 30 g/l) and 3 replications. The four tested seed sources are two seedling seed orchard (SSO) originated from Papua New Guinea provenance (namely group A and B), one SSO originated from Far North Queensland provenance (group C) and one SSO originated from a combining both provenances (group E). The treatment is given by  watering the seedlings from each provenance with saline solution in accordance with a predetermined concentration of 200 ml per day for 4 months. The observed parameters were stomatal index, length dan width of stomata, number and diameter of trachea, and chlorophyll content. The results showed that in general the differences in salt co ncentration provided a significant effect on anatomical response of A. mangium. Except for the length of stomata, seed source variations were significantly different for all parameters. Meanwhile, seed sources x salt level  interaction did not significantly affect the length and width of stomata. The higher the salt concentration, the lower the stomatal index and chlorophyll content. Conversely, the higher the salt concentration, the higher the amount of the tracheid. However the differences in salt concentration did not give a significant effect on diameter of tracheid. Overall, among the four tested seed sources, group B which is originated from Papua New Guinea provenancewas found to be the most tolerant seed sources to salt stress.